Performance of different abutment/implant joints as a result of a sealing agent - Seloto, Camila Berbel [UNESP] (2021)
Purpose: This in vitro study aimed to evaluate the effectiveness of a sealing agent in sealing the abutment/implant interface and the preload maintenance of retaining screws after mechanical cycling. Methods: Six groups (n = 12) were evaluated according to the abutment/implant system (external-hexagon implant and UCLA abutments, EHU; Morse taper implant and UCLA abutments, MTU; and Morse taper implant and flexcone abutments, MTF) and the presence of an anaerobic gel sealing agent (control group, no sealing agent; experimental group, sealing agent). Toluidine blue (0.7 μL) was inserted into each implant and the abutments were attached to the implants using a digital torque wrench to evaluate the sealing of the abutment/implant interface. The specimens were tested through mechanical cycling (1 × 106 cycles, 2 Hz, and 130 N). Dye release from the abutment/implant interface was analyzed using a spectrophotometer, and the reverse torque values were obtained using a digital wrench. Reverse torque and dye release data were measured after mechanical cycling and analyzed using ANOVA and Tukey’s test (α =.05). Results: All experimental groups showed higher reverse torque values than the control groups (P <.05). In general, the MTU and MTF experimental groups, as well as the MTF control group, showed no significant dye release at different periods (P >.05). Conclusions: The use of a sealing agent improved the preload maintenance of screw-retained implant-supported prostheses. The sealing agent was effective in sealing the Morse taper connection.